1991
DOI: 10.1128/jb.173.6.1938-1943.1991
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of an organophosphorus acid anhydrase from a halophilic bacterial isolate

Abstract: A moderately halophilic bacterial isolate has been found to possess high levels of enzymatic activity against several highly toxic organophosphorus compounds. The predominant enzyme, designated organophosphorus acid anhydrase 2, has been purified 1,000-fold to homogeneity and characterized. The enzyme is a single polypeptide with a molecular weight of 60,000. With diisopropylfluorophosphate as a substrate, the enzyme has optimum activity at pH 8.5 and 50 degrees C, and it is stimulated by manganese and cobalt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 9 publications
3
102
0
1
Order By: Relevance
“…Therefore, these data suggested that 2-HPA could be a product derived from an unstable intermediate rather than a true intermediate of the PA catabolic pathway. As it has been shown that the cis-dihydrodiols formed during the catabolism of different aromatic compounds readily dehydrate nonenzymatically under acidic conditions leading to the corresponding monohydroxy derivatives (2, 42), we checked whether 2-HPA could be also the product of dehydration of a dihydrodiol by monitoring the reported spectral changes associated with such decomposition (42). However, the UV spectrum of the supernatants from E. coli W14 cells containing the pAAD::Tn1000 derivative 3 (Fig.…”
Section: Identification Of the Paa Genes For The Catabolism Of Pa-wementioning
confidence: 99%
“…Therefore, these data suggested that 2-HPA could be a product derived from an unstable intermediate rather than a true intermediate of the PA catabolic pathway. As it has been shown that the cis-dihydrodiols formed during the catabolism of different aromatic compounds readily dehydrate nonenzymatically under acidic conditions leading to the corresponding monohydroxy derivatives (2, 42), we checked whether 2-HPA could be also the product of dehydration of a dihydrodiol by monitoring the reported spectral changes associated with such decomposition (42). However, the UV spectrum of the supernatants from E. coli W14 cells containing the pAAD::Tn1000 derivative 3 (Fig.…”
Section: Identification Of the Paa Genes For The Catabolism Of Pa-wementioning
confidence: 99%
“…Although this reaction is usually straightforward, it results in large quantities of a corrosive brine solution containing isopropyl methylphosphonic acid (IMPA) and sodium fluoride that must be further processed and may be subject to hazardous waste disposal. The same hydrolytic neutralization can be carried out under very mild conditions (neutral pH, room temperature) by catalysis of OPH enzymes (organophosphate hydrolases) (DeFrank and Cheng, 1991;Dave et al, 1993). The OPH catalyzed reaction is very rapid; 1 mg of enzyme can catalyze the complete hydrolysis (below 1 ppm) of 1 g of munition-grade GB in a 10% aqueous solution in less than 1 h (Harvey et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…The environmental problems caused by harmful chemical compounds, especially organophosphorus compounds, in environments with considerably high salt concentrations have been recognized for a long time [12,13]. Knowledge about degradation of pollutants in these environments, however, is still extremely limited [14][15][16].…”
Section: Fig 1 22-dichlorovynil Dimethyl Phosphate (Ddvp) Dichlorvosmentioning
confidence: 99%